Avaliação Química e Biológica in vitro dos extratos metanólicos das raízes e cascas do caule de Maclura tinctoria (L.) D. Don ex Steud - Barros, João Felipe da Silva (2021)
Maclura tinctoria, popularly known as amoreira or tatajuba, is a medium to large tree widely distributed throughout Brazil, occurring from Amazon to the south of the country. Its wood is widely used in carpentry and construction, due to its high strength. While in folk medicine, stem exudate and tea from bark are used as healing and anti-inflammatory potions. In this study, root and stem bark extracts were evaluated for their chemical composition and biological activity. The extracts were evaluated for antioxidant capacity and enzyme inhibition using pancreatic lipase and α-glycosidase enzyme inhibition assays. The polyphenolic compounds present in methanol extract of the stem bark were identified and quantified through chromatographic and solid phase extraction (SPE) techniques. Results showed antioxidant activity of extracts, roots (IC50 = 0.692 mg/mL) and stem bark (0.888 mg/mL), when compared to compounds already know as antioxidant agents, quercetin (0.057 mg/mL), rutin (0.133 mg/mL) and 3,5-di-tert-butyl-4-hydroxytoluene (0.175 mg/mL). In enzyme inhibition assays, both extracts showed inhibitory capacity. The methanol extract of stem bark stood out in inhibiting the pancreatic lipase enzyme (inhibition = 78.326 %), while the root extract was more effective in inhibiting the α-glucosidase enzyme (93.110 %). The chromatographic treatment enabled the quantification of flavonoids, xanthones and chalcones, highlighting the isolation and characterization of compounds morin, dihydromorin, (+)-afzelechin and norathyriol-6-Oglucoside, the last two compounds being new in this species.